Pengaruh pengeluaran pemerintah daerah sektor pendidikan dan kesehatan terhadap produk domestik regional bruto serta indeks pembangunan manusia di kalimantan timur - Agustina, Eka; Rochaida, Eny; Ulfah, Yana (INOVASI, 2016)
This study aimed to analyze and determine the effect of government spending for education and health sectors to gross domestic regional product and human development index in East Kalimantan province ranked. The data used in this research is secondary data in the years 2004-2013. The analytical tool used is path analysis (path analysis). The software used to perform the analysis is IBM SPSS Version 17:00. The analysis showed that the path coefficient between the Education Sector Expenditure (X1) 0.167, the line was not significant because t count at 0.790. Greater than Probability Value (sig) 0,455 > 0,050. The analysis showed that the path coefficient between Budget allocation for Health (X2) 0.815, the line was a significant effect for t count amounted to 3.861 (t count 3.861> t table 2,364), thus the pattern of these direct relationships, budget allocations for the health sector significantly influence gross domestic regional product, which is supported by Probability Value (sig) 0.006 < 0.050. The analysis showed that the path coefficient between (X1) 0,105, the line was not significant because t count at 0.675. Greater than Probability Value (sig) 0.525 > 0.050. Thus the pattern of this direct connection, the Education Sector Budget allocation not significant effect on the HDI. The analysis showed that the path coefficient between (X2) -0.272, the line was not significant because the value t count -1.028. Greater than Probability Value (sig) 0.334 > 0.050. Thus the pattern of this direct relationship, Health Sector Budget Allocation significant negative effect on the HDI. The analysis showed that the path coefficient between (Y) 1,150, the line was a significant effect for t count amounted to 4.291 while ttable 2.446 (t = 4.291> table = 2.446), thus the pattern of these direct relationships, gross domestic regional product significant positive effect on the HDI, which is supported by Probability Value (sig) 0,004 > 0,050. Results Test Analysis indirect influence, obtained Effect of Budget Allocation field of education (X1) to HDI (Y2) through gross domestic regional product (Y1) of 0.19205 (positive). Results Test Analysis indirect influence, obtained Effect of Budget Allocation for Health (X2) to HDI (Y2) through gross domestic regional product (Y1) of 0.93725.Keyword: Budget Allocation for Education and Health, GDRP, HDI.